THE EFFECTS OF ICT-BASED LEARNING ON STUDENTS' VOCABULARY MASTERY : a quasi experimental research in a junior high school in bandung - Hussain, Zakir (2017)
This study aimed to examine the effects of ICT-based learning using Wiki on EFL students' vocabulary mastery at a junior high school. The design of the present study was quasi-experimental study. The population of the study was 125 seventh graders in a junior high school in Bandung. The samples were two groups, Experimental group and control group. Each group comprised of 25 students. The instruments of the study were a pre-test and a post-test of vocabulary mastery. The data were analyzed by SPSS 16.0 for the windows. The findings revealed that there were significant differences at .05 level between experimental group and control group (df =49, t=2.02) which means students in the experimental group have scored higher than the control group. As a recommendation, teachers who are interested in teaching through ICT-based learning should provide an interesting topic on the wiki, let students chat while working online, assign them working at home and well prepare the facilities used in the class before starting the lesson. ;---Penelitian ini bertujuan untuk menguji pengaruh pembelajaran berbasis ITC dengan menggunakan Wiki pada penguasaan kosa kata para siswa di sekolah menengah pertama. Penelitian ini menggunakan desain eksperimental. Populasi dari penelitian ini adalah 125 siswa dari kelas tujuh di sekolah menengah pertama di Bandung. Terdapat dua sampel dalam penelitian ini yaitu, kelompok eksperimen dan kelompok kontrol. Masing-masing kelompok terdiri dari 25 siswa. Adapun instrumen yang digunakan pada penelitian ini adalah pre-test dan post-test mengenai penguasaan kosa kata. Data dianalisis dengan menggunakan SPSS 16.0 for Windows. Temuan penelitian ini menunjukkan adanya perbedaan yang signifikan pada tingkat 0,05 antara kelompok eksperimen dan kelompok kontrol (df = 49, t=2,02) yang berarti bahwa siswa di kelompok eksperimen memiliki skor yang lebih tinggi dari pada kelompok kontrol. Penelitian ini memberikan rekomendasi kepada guru yang tertarik dalam pengajaran dan pembelajaran berbasis ICT untuk memberikan topik yang menarik pada Wiki, memberikan kesempatan kepada siswa untuk berbicara saat berkerja secara online, serta memberikan tugas rumah dan juga menyediakan fasilitas yang akan digunakan di kelas sebelum memulai pembelajaran.